6x-9=-3x+63

Simple and best practice solution for 6x-9=-3x+63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-9=-3x+63 equation:



6x-9=-3x+63
We move all terms to the left:
6x-9-(-3x+63)=0
We get rid of parentheses
6x+3x-63-9=0
We add all the numbers together, and all the variables
9x-72=0
We move all terms containing x to the left, all other terms to the right
9x=72
x=72/9
x=8

See similar equations:

| 4(x+5)=150 | | 2(5y+6)-3=4y+2 | | -0.55=0.2(x-61/2) | | (5b*2)+(4b*2)=72 | | 8x+12=108+6x | | a/74=6.79 | | 15=3v-15 | | y2+12y=–7 | | −v−4=3v | | 5v+12=13 | | 5v2+12v=13 | | 3x+21=123 | | 3x+14=4x-26 | | 12(9x+3)=1008 | | 6.3r=45.36 | | 85z​ −18=824−2z​ | | a+21=-9 | | 8(2^x*3)=48 | | 14=-8m | | z+45=33 | | 7x=30-2 | | 7y−1=3y+11 | | 11x-9/3-10=3 | | 14n=n | | x/6-9=5 | | 7x/6-12=156 | | 15+p=-12 | | 3.25=2.5+r | | 15n-6.5=53.3 | | 15x/8+7=37 | | x/8=15/23 | | 90x=80x+75 |

Equations solver categories